Knowledge and application of biological control in oil palm plantations : Survey in Merlimau and Jasin, Melaka / Nurfariha Iman Taha - Iman Taha, Nurfariha (Faculty of Plantation and Agrotechnology, 2016)
Oil Palm are widely grown in tropical countries especially in Malaysia. The widespread use of this pesticide and insecticide chemical is causing the new bad effect to the environment and human health such as secondary pest outbreaks, resistance and hazards. They started using natural materials such using a biological control application to control the pest populations in the plantations. Biological control is the natural way that is aimed to pests and diseases. Biological control agent is the form of predators, parasitoids and pathogen. By doing this survey study, the existing knowledge of biological control among the managers and small holders of the oil palm plantation will be investigate. Furthermore, this survey indirectly help the managers and smallholders know the pro and cons of biological application compares to the using of chemical in their field. Besides, there have a different between the plantations which apply and without applying the biological control to reduce the pests and diseases.